Pengaruh Fraksi Volume Komposit Poliester Diperkuat Serat Rambut Manusia Dan Serabut Kelapa Terhadap Sifat Mekanik - akbar anggoro putra (Jurnal POLIMESIN, 2022)
Currently, composite applications range from the automotive, marine, and even aircraft sectors. One of the composites that have attracted a lot of attention from researchers is composites with natural fibers because natural fiber composites can be used as an alternative to synthetic or plastic materials. The low-density nature of natural fibers can provide good stiffness and strength as in fiberglass-reinforced composites. Coconut coir fiber and human hair waste are the basic materials for the manufacture of composites in this study. Because the amount is abundant so it is easy to obtain. The purpose of this study was to determine the effect of the variation of the best volume fraction of natural fiber composites with polyester matrix on the mechanical properties. The method used is hand layup with 3 variations of fiber volume fraction and polyester matrix, respectively 10:90, 15:85, and 20:80 and with the size of short hair fibers with a size of 3 cm and long coconut fibers with sizes according to the length of the print. The ratio of human hair fiber and coconut fiber is 1:1. Each fraction was tested 3 times to be more accurate. The results of the average tensile strength test with the largest ASTM D638 standard are at the volume fraction of 10:90 with a tensile strength of 19.2 MPa and the average impact test strength with the largest ISO 179-1 standard at the volume fraction of 20:80 is 17, 67 kJ/m². This study showed that the higher the fiber fraction in the composite, the lower the tensile strength but the higher the impact strength. Vice versa, the lower the fiber fraction in the composite, the tensile strength increases but the impact strength decreases.